Development and validation of a brief screening instrument for psychosocial risk associated with genetic testing: a pan-Canadian cohort study. Issue 3 (13th March 2013) - Esplen, Mary Jane; Cappelli, Mario; Wong, Jiahui; Bottorff, Joan L; Hunter, Jon; Carroll, June; Dorval, Michel; Wilson, Brenda; Allanson, Judith; Semotiuk, Kara; Aronson, Melyssa; Bordeleau, Louise; et al.
Abstract : Objectives: To develop a brief, reliable and valid instrument to screen psychosocial risk among those who are undergoing genetic testing for Adult-Onset Hereditary Disease (AOHD). Design: A prospective two-phase cohort study. Setting: 5 genetic testing centres for AOHD, such as cancer, Huntington's disease or haemochromatosis, in ambulatory clinics of tertiary hospitals across Canada. Participants: 141 individuals undergoing genetic testing were approached and consented to the instrument development phase of the study (Phase I). The Genetic Psychosocial Risk Instrument (GPRI) developed in Phase I was tested in Phase II for item refinement and validation. A separate cohort of 722 individuals consented to the study, 712 completed the baseline package and 463 completed all follow-up assessments. Most participants were female, at the mid-life stage. Individuals in advanced stages of the illness or with cognitive impairment or a language barrier were excluded. Interventions: Phase I: GPRI items were generated from (1) a review of the literature, (2) input from genetic counsellors and (3) phase I participants. Phase II: further item refinement and validation were conducted with a second cohort of participants who completed the GPRI at baseline and were followed for psychological distress 1-month postgenetic testing results. Primary and secondary outcome measures: GPRI, Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HAM-A), Brief Symptom Inventory (BSI) and Impact of Event Scale (IES). Results: The final 20-item GPRI had a high reliability—Cronbach's α at 0.81. The construct validity was supported by high correlations between GPRI and BSI and IES. The predictive value was demonstrated by a receiver operating characteristic curve of 0.78 plotting GPRI against follow-up assessments using HAM-D and HAM-A. Conclusions: With a cut-off score of 50, GPRI identified 84% of participants who displayed distress postgenetic testing results, supporting its potential usefulness in a clinical setting.